Factors Of Erp Perceived Value And Organizational Performance At The Pre-Implementation Phase: Organisational Learning Capability As A Moderator - Mohamed Soliman, Mohamed Soliman (2020)
Higher education institutions (HEIs) are challenged to sustain the high-level information systems to generate complex real-time reports. Also, their need for digital transformation to stay competitive. Enterprise Resource Planning (ERP) systems, through its integration characteristic, can provide tailored solutions for effective resource allocation and better decision making. Even though ERP systems increase organisational innovation, most Egyptian HEIs have not implemented ERP, showing ERP is not perceived as innovation capability. Therefore, this study aims to develop a model of ERP perceived value at the pre-implementation phase. This study explored the insights of 112 Egyptian HEIs. Based on the previous studies, this study predicts the factors of ERP perceived value among HEIs through linking three prominent frameworks; Technology-Organization-Environment (TOE) framework, technology readiness index (TRI), and resource-based view (RBV). The TOE factors include relative advantage, technological capability, top management support, perceived technical competence, and competitive pressure. The research investigates the factors of ERP perceived value, further examines the impact of ERP perceived value on organizational performance and the moderating effects of organisational learning capability (OLC).